THE COMMUNITY KNOWLEDGE ON USE OF TRADITIONAL MEDICINE FOR SELF-MEDICATION IN MANGNGI HAMLET, NOSU SUB-DISTRICT - Indrayani, Ferna; Muin, Rahmatullah; Datu, Jumiati (Journal of Pharmaceutical Science and Herbal Technology, 2024)
Traditional medicines are ingredients or ingredients in the form of plants, animals, minerals, galenic preparations or mixtures of various ingredients that have been used for generations as medicine and can be used by the community in accordance with applicable norms. Self-medication or self-medication is an attempt by the community to treat complaints or symptoms of illness on their own without the help of medical personnel. This study aims to determine the description of public knowledge about the use of traditional medicine as self-medication in Mangngi' Hamlet, Nosu District. The type of research used is descriptive research. The research was conducted on June 20-22 2023 for respondents who live in Dusun Mangngi' with the number of respondents using a questionnaire. The description of the use of traditional medicine as self-medication in Dusun Mangngi' is that people who know well (94.74%) and less (5.26%).